Investigation on microstructure and oxidation behavior of Cr-modified aluminide coating on γ-TiAl alloys - Jafarian, H.R.; Mirzamohammdi, S.; Sabour Rouhaghdam, A.; Aliofkhazraei, M. (Фізико-хімічна механіка матеріалів, 2011)
Microstructure and oxidation behavior of aluminide coating has been investigated. The layers were examined by optical microscopy, scanning electron microscopy (SEM) equipped with EDS and X-ray diffraction method. The isothermal oxidation behaviors of samples were investigated at 950°C for 200 h. The results indicated that TiAl₃ were formed on substrate. In addition, aluminide coating improved the oxidation resistance of γ-TiAl alloys by forming a protective alumina scale. Moreover, during oxidation treatment the interdiffusion of TiAl₃ layer with γ-TiAl substrate results in depletion of aluminum in the TiAl₃ layer and growth of TiAl₂ layer. After oxidation treatment the coating layer maintained a microstructure with phases including TiAl₃, TiAl₂ and Al₂O₃. Досліджено мікроструктуру алюмінідного покриву та його поведінку під час високотемпературного окислення. Шари алюмінідів титану вивчали за допомогою оптичної мікроскопії, сканівної електронної мікроскопії (SЕМ) з використанням дисперсного рентгеноспектрометра (EDS) та рентгенівським дифракційним методом. Випробовування проводили при 950°C впродовж 200 h. Встановлено, що на підкладці з титанового сплаву утворився TiAl₃. Покрив з алюмініду титану покращує стійкість до окислення сплавів з γ-TiAl, утворюючи захисну плівку з оксиду алюмінію. Під час окислення дифузійна взаємодія TiAl₃ з підкладкою γ-TiAl спричиняє зменшення кількості алюмінію у шарі TiAl₃ та збільшення шару TiAl₂. Після окислення в покриві утворюється мікроструктура з фазами, що містять TiAl₃, TiAl₂ та Al₂O₃. Исследовано микроструктуру алюминидного покрытия и его поведение при высокотемпературном окислении. Слои алюминида титана изучали с помощью оптической микроскопии, сканирующей электронной микроскопии (SЕМ) с использованием дисперсного рентгеноспектрометра (EDS) и рентгеновским дифракционным методом. Испытания проводили при 950°C в течение 200 h. Установлено, что на подкладке из титанового сплава образовался TiAl₃. Покрытие из алюминида титана улучшает стойкость к окислению сплавов из γ-TiAl, образовывая защитную пленку из окисла алюминия. Во время окисления диффузионное взаимодействие TiAl₃ с подкладкой γ-TiAl влечет уменьшение количества алюминия в слое TiAl₃ и увеличение слоя TiAl₂. После окисления в покрытии образуется микроструктура с фазами, которые содержат TiAl₃, TiAl₂ и Al₂O₃.